Case Report: Genetic Double Strike: VEXAS and TET2-Positive Myelodysplastic Syndrome in a Patient With Long-Standing Refractory Autoinflammatory Disease - Lötscher, Fabian; Seitz, Luca; Simeunovic, Helena; Sarbu, Adela-Cristina; Porret, Naomi A.; Feldmeyer, Laurence; Borradori, Luca; Bonadies, Nicolas; Maurer, Britta (Frontiers in Immunology, 2022)
Somatic genetic mutations involving the innate and inflammasome signaling are key drivers of the pathogenesis of myelodysplastic syndromes (MDS). Herein, we present a patient, who suffered from a long-standing refractory adult-onset autoinflammatory syndrome (AIS), previously interpreted as various distinct rheumatic disorders. Developing pancytopenia and particularly macrocytic anemia prompted the screening for a hematological malignancy, which led to the diagnosis of a TET-2-positive MDS. The impressive and continuously changing range of organ involvement, with remarkable refractoriness to anti-inflammatory treatment, exceeded the common auto-inflammatory phenotype of MDS patients. This prompted us to suspect a recently discovered disease, characterized by somatic mutations of the UBA1 gene: the VEXAS (Vacuoles, E1 enzyme, X-linked, Autoinflammatory, Somatic) syndrome, which was ultimately confirmed by genetic testing. Reevaluation of previous bone marrow biopsies showed the presence of characteristic vacuoles in myeloid- and erythroid progenitor cells. Our case illustrates that the triad of an unresponsive multisystemic autoinflammatory disease, hematological abnormalities and vacuoles in myeloid- and erythroid progenitors in the bone marrow biopsy should prompt screening for the VEXAS syndrome.